Effects of drilling parameters and aspect ratios on delamination and surface roughness of lignocellulosic HFRP composite laminates. Issue 7 (9th September 2015) - Ismail, Sikiru Oluwarotimi; Dhakal, Hom Nath; Dimla, Eric; Beaugrand, Johnny; Popov, Ivan
ABSTRACT: Hemp fibre‐reinforced polycaprolactone (HFRP) composite has inherent good mechanical properties and benefits which include remarkably high specific strength and modulus, low density, and renewability. No doubt, these properties have attracted wider applications of HFRP composite in engineering applications. This paper presents an investigation on the influence of drilling parameters and fibre aspect ratios, AR (0, 19, 26, 30, and 38) on delamination damage factor and surface roughness of HFRP composite laminates utilising high speed steel twist drills under dry machining condition. Taguchi's technique was used in the design of experiment. The results obtained show that increase in cutting speed reduces delamination factor and surface roughness of drilled holes, whereas increase in feed rate causes increase in both delamination factor and surface roughness. Feed rate and cutting speed had the greatest influence on delamination and surface roughness respectively when compared with aspect ratio, while an increase in fibre aspect ratios leads to a significant increase in both delamination factor and surface roughness. The optimum results occurred at cutting speed and feed rate (drilling parameters) of 20 mm/min and 0.10 mm/rev, respectively, when drilling sample of AR 19. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 42879. Abstract :